Barriers to Accessing Video-Based Telehealth Appointments at a Community Veterinary Clinic During the COVID-19 Pandemic - Naimark, Alena M.; Elwood, Stella E.; McCobb, Emily; Kragen, Benjamin; King, Erin K.; Wolfus, Greg (Frontiers in Veterinary Science, 2022)
Objective To assess veterinary needs of clients with low socioeconomic status during the COVID-19 pandemic, to explore the impact of the pandemic on marginalized communities, and to understand perceptions regarding barriers and incentives of telehealth appointments as a method to increase care access. Sample 205 active Community Veterinary Medicine Clinic clients at Tufts at Tech Community Veterinary Clinic in Worcester, MA. Procedures This cross-sectional study used a survey-based method to assess veterinary needs of clients with low socioeconomic status during the COVID-19 pandemic. The survey measured client perceptions regarding potential barriers and incentives of telehealth appointments. Participants were randomly sampled from a list of active clients and completed the survey either by email or over the phone. The survey was available in both English and Spanish. Clients who completed the questionnaire received credit for a free examination. Results A total of 205 clients submitted survey responses. Factors affecting access to veterinary care were impacted by the COVID-19 pandemic. Access to reliable internet in the home was reported by 87% (n = 177) of participants. Digital access was correlated with education when controlling for race, income, age, and gender. Education was predictive of comfort with using video-chat (χ2 = 65, df = 24, p ≤ 0.01) and of whether or not clients reported need for assistance for using video-chat (χ2 = 52, df = 18, p ≤ 0.01). Patient education level was significantly predictive of wanting to use telehealth for at least one type of appointment (p ≤ 0.05). Conclusions and Clinical Relevance The findings indicate that implementing telehealth services at this Community Medicine Clinic is feasible for much of the active clientele and offers a new avenue to provide veterinary care during times of social distancing restrictions and beyond.